2019
DOI: 10.1002/slct.201900387
|View full text |Cite
|
Sign up to set email alerts
|

1,1,1,4,4,4‐Hexafluorobut‐2‐yne (HFB) as a Versatile Dipolarophile for [3+2] Cycloaddition with 1,3‐Dipoles toward Azoles with Adjacent CF3 Groups

Abstract: This project involves the syntheses of novel pyrazoles, pyrazolines and isoxazoles with two CF3 groups via 1,3‐dipolar cycloaddition reaction of 1,1,1,4,4,4‐hexafluorobut‐2‐yne (HFB) with diazocompounds, azomethine imines and nitrile oxides, respectively. Conditions for these azoles preparation differ in catalyst‐free mild manners and are applicable to a wide range of substrates, while demonstraiting a high functional group tolerance with yields of target heterocycles from moderate to excellent. Indeed, pyrazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In 2019, Yagupolskii and Peng also showed that diazoalkane 183 reacted with alkyne 177 at room temperature to afford pyrazole 184 in 35% yield (Scheme ). In the same study, the authors also elaborated the synthesis of bis­(trifluoromethyl)-substituted pyrazoles from diazocarbonyl compounds and acetylene 177 (Scheme ). The reaction proceeded at room temperature in dimethoxyethane to give products of type 185 – 187 in 90–97% yield.…”
Section: Preparation Of Fluoroalkyl-substituted Pyrazolesmentioning
confidence: 99%
“…In 2019, Yagupolskii and Peng also showed that diazoalkane 183 reacted with alkyne 177 at room temperature to afford pyrazole 184 in 35% yield (Scheme ). In the same study, the authors also elaborated the synthesis of bis­(trifluoromethyl)-substituted pyrazoles from diazocarbonyl compounds and acetylene 177 (Scheme ). The reaction proceeded at room temperature in dimethoxyethane to give products of type 185 – 187 in 90–97% yield.…”
Section: Preparation Of Fluoroalkyl-substituted Pyrazolesmentioning
confidence: 99%
“…The common approaches for the synthesis of trifluoromethyl pyrazole compounds are the [3 + 2] cycloaddition of trifluorodiazoethane or 4-trifluoromethylsydnones with alkynes; [7] the cyclocondensation of hydrazines with trifluoromethyl 1,3diketones or trifluoromethyl α,β-ynones compounds; [8] the [3 + 2] cycloaddition of trifluoromethyl alkenes or alkynes with diazo compounds. [9] These methods usually produce 5-substituted 3-trifluoromethyl pyrazoles. There are only several reports for the synthesis of 4-substituted 3-trifluoromethyl pyrazoles.…”
Section: Introductionmentioning
confidence: 99%
“…Using bis(trifluoromethyl)acetylene as the dipolarophile in the reactions with α-diazo ketones, high yields of medicinally important bis(trifluoromethyl)pyrazoles 86 can be obtained ( Scheme 50 ) [ 85 ].…”
Section: Cyclic α-Diazo Ketonessmentioning
confidence: 99%